Working Memory With Emotional Distraction in Monolingual and Bilingual Children - Janus, Monika; Bialystok, Ellen (Frontiers in Psychology, 2018)
Extensive work has demonstrated the benefits of bilingualism on executive functioning (EF) across the lifespan. Concurrently, other research has shown that EF is related to emotion regulation (ER), an ability that is integral to healthy socio-emotional development. However, no research to date has investigated whether bilingualism-related advantages in EF can also be found in emotional contexts. The current study examined the performance of 93 children who were 9-years old, about half of whom were bilingual, on the Emotional Face N-Back Task, an ER task used to assess the interference effect of emotional processing on working memory. Bilingual children were more accurate than monolingual children in both 1-back and 2-back conditions, but were significantly slower than monolingual children on the 2-back condition and demonstrated speed-accuracy tradeoffs. There were significant effects of emotional valence on reaction time, but these did not differ across language groups. These results confirm previous research showing better EF performance by bilinguals, but no differences in ER were found between language groups. Findings are discussed in the context of our current understanding of the ER literature with potential implications for previously unexplored differences between monolingual and bilingual children.